NUTRIONAL NEEDS OF ATHLETES - Pandey Shruti; Singh Vasudeva (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Aim - is to provide a comprehensive information regarding the nutritional needs of athletes, followed by female athletes who have a higher necessity for Iron. Sports and nutrition are directly related to each other. Taking into consideration the fact that sports person need more energy to carry out their sporting activity effectively, it becomes of prime importance to take care for sports performance. Athletes must supposedly eat the perfect ratio of Protein, carbohydrate and fat at each meal and snack to control the hormonal systems and thus reach their maximum performance and ideal weight .The carbohydrate/protein/fat ratio of the 40-30-30 diet allegedly maintains the proper balance between the hormones insulin and glucagon. The present review focuses on the intake for a wholesome nutrient and well balanced diet for better performance among male as well as female athletes.